Assessment of knowledge regarding prediabetes among a sample of family physicians in (Baghdad city) - Taymaa Majd Hameed,; Yossra Khalaf Hanoon, (Journal of the Pakistan Medical Association, 2024)
Objectives: To assess the level of knowledge among family physicians regarding prediabetes. Method: The cross-sectional study was conducted from March 1 to June 30, 2020, at primary healthcare centers in Al-Karkh and Al-Rusafa health directorates of Baghdad, Iraq, after approval from the ethics review committee of the College of Medicine, Mustansiriyah University, Baghdad. The sample comprised family physicians of either gender. Data was collected using an pre-designed, structured questionnaire that was disseminated online. Data was collected using SPSS 25. Results: Of the 145 questionnaires distributed, 113(78%) were returned duly filled; 99(87.6%) females and 14(12.4%) males. The overall mean age was 34.21±5.8 years (range: 26-49 years), The knowledge level was good in 60(53.1%) cases, and 59(52.2%) suggested screening programmes as a preventive measure. Good level of knowledge was significantly associated with having diabetes or family member with diabetes 44(51.7%), attending training courses 37(44.1%) and professional experience >10 years 15(25%). Conclusion: More than half the respondents had a good level of knowledge about prediabetes. There is a need to improve the knowledge of physicians further about prediabetes. Key Words: Prediabetic, Metformin, Counseling, Family Physicians, Electronics.